Direito de retenção no direito brasileiro: proposta de sistematização - Catuzzo Junior, Dante Soares (2011)
This work aims to propose a way to systematize the right of retention in Brazilian law. The research in question was developed through the analysis of legal texts about the institute of Brazilian and foreign law, the national and foreign doctrine and jurisprudence. The object of study is the right of retention, a particular way to ensure obligations, whereby the creditor keeps under his/her power, upon a new title, the mischief thing, that he/she already rightly holds, beyond the moment it should be delivered, with the purpose of imposing and assuring the voluntary compliance with an obligation to give such a sum of money in cash, which keeps a connect relationship with the thing withheld. The author discoursed about the essential elements to understand the right of retention of the Brazilian legal system, such as: origin and evolution, legal structure, concepts, features, legal basis, function, application sphere, requirements, effects, hypothesis of acceptance, types of guardianship, termination causes and foreign legislation overview on the institute. Upon said general concepts, the author intended to contribute to the best interpretation and application, by law professionals, of the right of retention institute and update the study of this theme before the existing legislation in the country